2022
DOI: 10.3390/app12104962
|View full text |Cite
|
Sign up to set email alerts
|

Joining of CFRT/Steel Hybrid Parts via Direct Pressing of Cold Formed Non-Rotational Symmetric Pin Structures

Abstract: In this study, quasi-unidirectional continuous fiber reinforced thermoplastics (CFRTs) are joined with metal sheets via cold formed cylindrical, elliptical and polygonal pin structures which are directly pressed into the CFRT component after local infrared heating. In comparison to already available studies, the unique novelty is the use of non-rotational symmetric pin structures for the CFRT/metal hybrid joining. Thus, a variation in the fiber orientation in the CFRT component as well as a variation in the no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…The undercuts could be sufficiently filled with matrix and fibres during joining and had a positive effect on the load-bearing capacity under pull-out load compared to a cylindrical pin without undercut. In addition to varying undercut geometries, the geometry of extruded pins made of DP600 when pressed directly into GF-PP was also investigated in [24] in order to investigate the influences of polygonal, oval and cylindrical pins on the joint formation and the load-bearing capacity of the joint. It was shown that a cylindrical pin is advantageous for an isotropic behaviour of the joint, but a polygonal pin can be advantageous especially under a predominant loading direction.…”
Section: Polygonal Oval Cylindricalmentioning
confidence: 99%
“…The undercuts could be sufficiently filled with matrix and fibres during joining and had a positive effect on the load-bearing capacity under pull-out load compared to a cylindrical pin without undercut. In addition to varying undercut geometries, the geometry of extruded pins made of DP600 when pressed directly into GF-PP was also investigated in [24] in order to investigate the influences of polygonal, oval and cylindrical pins on the joint formation and the load-bearing capacity of the joint. It was shown that a cylindrical pin is advantageous for an isotropic behaviour of the joint, but a polygonal pin can be advantageous especially under a predominant loading direction.…”
Section: Polygonal Oval Cylindricalmentioning
confidence: 99%